Strategic differences: Al Qaeda's Split with the Islamic State of Iraq and al-Sham - Turner, John (Routledge Journals, Taylor & Francis Ltd, 2015)
As part of the next phase of the Global Jihad, al Qaeda has been committed to winning popular support among Muslims. Ayman al-Zawahiri and the al Qaeda inner circle recognise that a global terror movement and civil conflicts in the Middle East, brought about by the Arab revolutions, necessitate different operational methods. As such, they have disavowed the Islamic State of Iraq and al-Sham for their insubordination and unconstrained tactics, a move that has implications for the Middle East, international relations, the legitimacy of the al Qaeda leadership, and the future of the Global Jihad.
Keywords: Caliphate; terrorism; ISIS; Jihadism; Arab Spring; Iraq; Salafi; Middle East; al Qaeda; Syria